2018
DOI: 10.1016/j.ihj.2018.10.412
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of QRS duration with myocardial blush grade as a marker of myocardial reperfusion in primary percutaneous coronary intervention

Abstract: BackgroundThe association between duration of QRS and myocardial reperfusion is not very well established. Our aim was to assess the relationship between measurements of QRS duration and myocardial blush grade (MBG) in patients with ST-elevation myocardial infarction (STEMI) who were treated with a primary percutaneous coronary intervention (PCI).MethodsBetween January 2016 and June 2017, 200 patients with STEMI who presented within 12 h of symptom onset and taken up for primary PCI were analyzed with electroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…9 Three studies (Yusuf et al, Ilkay et al, and Kacmaz et al) mentioned a third investigator who resolves the discordance between the two investigators. 8,11,12 Karahan et al did not mention a third investigator but reported an intra-and interobserver agreement of 95% and 90%, respectively, which is similar to that in Yusuf et al's study, which employed the third investigator to resolve the dispute. 2,11 Ozcan et al hypothesized that fQRS correlated with the extent of myocardial damage due to a lowered left ventricular ejection fraction in their study and that better microvascular perfusion leads to the resolution of fQRS.…”
Section: Subgroup Analysissupporting
confidence: 53%
See 3 more Smart Citations
“…9 Three studies (Yusuf et al, Ilkay et al, and Kacmaz et al) mentioned a third investigator who resolves the discordance between the two investigators. 8,11,12 Karahan et al did not mention a third investigator but reported an intra-and interobserver agreement of 95% and 90%, respectively, which is similar to that in Yusuf et al's study, which employed the third investigator to resolve the dispute. 2,11 Ozcan et al hypothesized that fQRS correlated with the extent of myocardial damage due to a lowered left ventricular ejection fraction in their study and that better microvascular perfusion leads to the resolution of fQRS.…”
Section: Subgroup Analysissupporting
confidence: 53%
“…8,11,12 Karahan et al did not mention a third investigator but reported an intra-and interobserver agreement of 95% and 90%, respectively, which is similar to that in Yusuf et al's study, which employed the third investigator to resolve the dispute. 2,11 Ozcan et al hypothesized that fQRS correlated with the extent of myocardial damage due to a lowered left ventricular ejection fraction in their study and that better microvascular perfusion leads to the resolution of fQRS. 13 This may indicate that fQRS might be because of poor microvascular perfusion that resulted in alteration of electrical activities, resulting in a different pattern of depolarization.…”
Section: Subgroup Analysissupporting
confidence: 53%
See 2 more Smart Citations
“…The real-time myocardial perfusion imaging with Myocardial Blush determination Grade (MBG) was used to measure myocardial perfusion [23]. The MBG was scored during angiographic analysis according to the conventional method [24].…”
Section: Real-time Myocardial Perfusion Imaging Determinationmentioning
confidence: 99%